THE INFLUENCE OF EDUCATIONAL ADMINISTRATION ON TEACHER PERFORMANCE AT SMA NEGERI 1 SERBAJADI, SERBAJADI DISTRICT, DELI SERDANG REGENCY - Ramadha Yanti Parinduri; Khairuddin Tampubolon; Barham Siregar (RADJA PUBLIKA, 2023)
The effect of educational administration on teacher performance at SMA Negeri 1 Serbajadi according to the hypothesis and from the observations of researchers is quite significant. This study aims to determine how much influence the educational administration has had on teacher performance at SMA Negeri 1 Serbajadi. This research method uses quantitative research methods. The sample is teachers at SMA Negeri 1 Serbajadi, a total of 37 people. The data processing method was carried out using SPSS software version 26. The results of the study: 1) From the results of the t test analysis, it is known that the sig. for the effect of the independent variable Education Administration on the dependent variable Teacher Performance is: 0.006 <0.05 and the t-count value is 3.526 > t table 2.026 so that it can be concluded that H is accepted, meaning that there is an influence of the independent variable Education Administration on the dependent variable Teacher Performance. 2) the output of the F test is known to be the sig. for the independent variables of Education Administration and other external elements simultaneously on the dependent variable Teacher Performance is 0.006 <0.05 and the calculated F value is 22.330 > F table 4.08, so it can be concluded that Ha is accepted means that there is influence of the Education Administration variables and other external elements simultaneously on teacher performance variable. 3) Based on the test results of the coefficient of determination (R2) it is known that the value of R Square is 0.862,